Análisis de los conflictos ambientales en interfases urbano-rurales (2009)
The article provides some general outlines about a first approach to the analysis of the environmental conflicts in Bogotá. Equally, it intended to propose the concept environmental conflict in the analysis of situations which, further environmental degradation, involve complex social-political dynamics. Two cases studies: Eastern Hills and Tunjuelo River, reveal the importance to identify socio ecological systems and territories where there are environmental conflicts. Finally, some proposals elaborated by environmental and social movements from Bogotá are presented, and it provides importantconcepts in the construction of politicians that impact in the territorial planning